72 Application of guidelines for ICD therapy: real-world experience. (17th July 2020) - Abraham, George; Thomas, Rebecca; Chousou, Panagiota; Pugh, Peter
Abstract : Introduction: The implantable cardioverter defibrillator (ICD) is an important treatment option for heart failure patients, protecting against sudden cardiac death. Current guidelines highlight left ventricular (LV) systolic function as the principal measure, for most patients, used to decide which patients receive ICD implantation. Referral for ICD implant is dependent upon recognition of the indication by the patient's physician. It is also recognised that sudden death risk is not solely a function of LV systolic function and guidelines could potentially exclude patients at risk of sudden death. We wished to ascertain how many patients presenting with life-threatening ventricular arrhythmias were already known to have an indication for ICD therapy, how many fell outside of current guidelines for primary prevention and, among the latter, what the underlying cardiac diagnoses were. Methods: In a 5-year single-centre retrospective study within a large teaching hospital, we used the hospital electronic patient record to identify patients admitted with new presentation of ventricular arrhythmia, who did not have an ICD in-situ. Case-notes were reviewed to identify whether patients already had a known indication for ICD implant and to determine the cardiac background. Results: Of 779 inpatient admissions with a code for ventricular arrhythmia, 302 patients were found to have had life-threatening arrhythmia. Of these, 79 had already received ICD implant. The clinical status of the remaining 223 patients is shown in Table 1 . After excluding patients with acute provocation (68) and 21 patients with severe LV impairment deemed ineligible for ICD therapy, 128 surviving patients were considered eligible to receive ICD implantation. Among these, 23 patients (18%) had a previously known guideline-based indication for primary prevention ICD treatment, of whom 10 died without leaving hospital (43.5%). 53 patients (41%) had structural heart disease not meeting criteria for primary prevention ICD (Table 2 ). Conclusions: Nearly one fifth of patients presenting to hospital with life-threatening ventricular arrhythmia and eligible for ICD therapy already had an identified indication for primary prevention ICD that had gone unrecognised, leading to potentially avoidable deaths. Two fifths of patients had cardiac disease falling outside of primary prevention guideline criteria. More widespread understanding of guidelines for recommending ICD therapy is important for ensuring that this treatment is offered to all eligible patients. This study suggests that current guidelines are unsatisfactory in identifying a substantial proportion of patients who may benefit from primary prevention ICD implantation. Conflict of Interest: none